Analisis Diksi Akademik pada Judul Artikel Jurnal Multidisiplin Ilmu Akademik (JMIA) Volume 3 Nomor 2 Tahun 2026 - Lolo Mesliana Cibro; Tessalonika Simangungsong; Nur Syakila; Randi Simarmata; Jakaria (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The purpose of this study is to describe the use of academic diction in article titles in the Multidisciplinary Journal of Academic Sciences (JMIA) Volume 3 Number 2 of 2026. Diction is an important element in writing scientific papers because it functions to convey ideas precisely, clearly, and in accordance with the characteristics of scientific language. This study applies a qualitative descriptive approach. with data sources in the form of 15 article titles selected from JMIA Volume 3 Number 2 of 2026. The data collection process was carried out through documentation, reading, and taking notes. Data were analyzed by identifying, grouping, and describing academic diction contained in the article titles. The results of the study show that there are various dominant academic dictions used, such as analysis, implementation, evaluation, transformation, optimization, urgency, perspective, and effectiveness. These dictions can be included in various categories, namely research diction, application diction, change diction, conceptual diction, and urgency diction. The use of academic diction in article titles serves to clarify the focus of the research, indicate the purpose of the research, and build the scientific character of a written work. Thus, choosing the right diction in the article title plays an important role in improving the quality of scientific communication and making it easier for readers to understand the research content.